Adaptive learning design based on local wisdom texts in Indonesian language classes: A literature review - Khairunnisa, Khairunnisa; Huriyah, Huriyah; Mahmudah, Mahmudah (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3768, 2025)
This study explores the conceptual integration of adaptive learning design with local wisdom-based texts in Indonesian language education. As learning technologies increasingly emphasize personalization, there remains a gap in how these adaptive systems can meaningfully incorporate Indonesia’s diverse cultural contexts. The research synthesizes findings from 19 national and international studies published between 2015 and 2025 related to adaptive learning, digital literacy, and local wisdom-based pedagogy, using a systematic literature review. The analysis reveals three major dimensions of integration: technological adaptivity, pedagogical mediation, and cultural contextualization. Technological adaptivity focuses on the use of AI, big data, and learning analytics to personalize content and feedback, while pedagogical mediation emphasizes the teacher’s role as a cultural interpreter and facilitator of humanistic learning. Cultural contextualization highlights the significance of local texts, values, and narratives as authentic learning materials that shape students’ identity and moral development. The resulting conceptual model, termed the Culturally Adaptive Learning Framework (CALF), proposes that adaptive learning should be “adaptive by data, humanized by culture.” This approach promotes a holistic view of language education that balances technological innovation with cultural values, aiming to foster literacy, inclusivity, and character formation among Indonesian elementary students.